Rural development and change : a case study of a Bangladesh village - Barkat-e-Khuda. (Dhaka : University Press, 1988)
Empirical study on Sriballabhpur, a village in Comilla-Kotwali Upazila, Bangladesh, during 1979-1981.
Includes index.
Bibliography: p. [140]-153.
Keywords: Rural development -- Bangladesh -- Sriballabhpur -- Case studies; Sriballabhpur (Bangladesh) -- Population -- Case studies